Supporting Users in Creating Pedagogically Sound Personalised Learning Objects - WADE, VINCENT PATRICK; DAGGER, DECLAN; CONLAN, OWEN (Springer, 2008)
Successful eLearning is predicated on the application of pedagogies appropriate to online education that respond to the capabilities and needs of the learners. Typically, designing and assembling personalized learning objects that respond to the pedagogical needs of a variety of different learners is an expensive and time-consuming process requiring both domain and educational expertise. Educators have the domain expertise and formal or informal pedagogical knowledge to create quality learning objects. However, they lack the tools and often the specific knowledge of online pedagogical approaches that make it time efficient for them to do so. This paper describes the motivation behind, the workflow supported by and the evaluation of the LO Generator, a tool that offers personalized support and scaffolding for users, who are not necessarily content creation or pedagogical experts, in assembling pedagogically sound personalized learning objects.
PUBLISHED
Keywords: Learning Object Creation; eLearning